Analysis of Approaches to the Development of Regional Calendars of Preventive Vaccinations against current infections in the constituent entities of the Russian Federation - E. N. Ponomareva; R. V. Polibin; N. D. Pakskina; V. N. Gorodin; E. Yu. Malinnikova (Эпидемиология и вакцинопрофилактика)
Relevance. The study of additional organization of vaccination in the regions of the country is an important task, especially in the context of global challenges associated with infectious diseases.Aim. To analyze the existing regional calendars of preventive vaccinations in the subjects of the Russian Federation.Result. A number of Russian regions provide additional vaccination as part of regional preventive vaccination calendars. Some regions create additional programs or comprehensive plans to organize immunoprophylaxis.Conclusion. Regional calendars of preventive vaccinations allow to adapt vaccination programs to modern conditions and can be considered as a tool oftransitional period of implementation of the strategy of development of immunoprophylaxis of infectious diseases for the period up to 2035, approved by the order of the Government of the Russian Federation from 29.03.2021 № 774-r in part by including additional vaccinations against vaccine-preventable infections, taking into account the epidemic situation and the presence of high-risk groups of infection in the region.